(untitled) (The Pakistan Development Review, 2016)
The book is divided into two parts consisting of eight chapters, including the introductory and concluding chapters, and an epilogue. It is a 304 page book including notes and references, which are not only interesting but are very helpful for any reader interested in the topic. The introductory chapter sets the stage for the reader, introducing her to the diversity of nations living in the geographical boundaries of Pakistan and points to the failure of their integration in the state project. The author also touches upon the ethnic and nationalistic struggles played out in Pakistan throughout history and their relationship with the politics of the left. Furthermore, he reiterates that mainstream discourse on Pakistan’s history presents the struggle for separate nation in unified India as a struggle of a monolith Muslim nation in the sub-continent largely ignoring the ethnic, cultural and linguistic diversity of these Muslims, thereby undermining their aspirations for freedom, self-determination and autonomy. The Bengali and the Baloch freedom movements have been cited as examples of what he calls the “collective amnesia” of the nation and notes that resistance, or left-leaning, movements have also been largely ignored in mainstream discourses on the history of Pakistan.